Correlation between Dietary Glycemic Index and Blood Lipids Abnormality as a Main Risk Factor of Atherosclerosis in Healthy Women from Ahvaz - Farideh Shishebor; zahra shamekhi; Majid Karandish; Mahmood Latifi (Shiraz University of Medical Sciences, 2016)
Background: Atherosclerosis and subsequent coronary artery disease is the leading cause of death in Iranian population. High serum lipid levels, especially the elevated level of low-density lipoprotein (LDL), have been shown to be strongly related to the development of atherosclerosis. The relationship between dietary glycemic index (GI) and lipid profile, particularly in nonwestern populations, has not been well studied; also, the result of studies are inconsistent. The aim of this study was to evaluate the relationship between dietary glycemic index (GI) and main risk factor of atherosclerosis including abnormal blood lipid levels in healthy women. Methods: This cross-sectional study was done to investigate the associations between dietary GI and lipid profile. The subjects were 87 female personnel of Ahvaz Jundishapur University of Medical Sciences aged 25-55 y; they were recruited randomly. Dietary GI was calculated from six 24 hour recalls (including 4 usual days and 2 holidays). Results: The mean of dietary GI was 72.1±4.07. After adjustment for potential dietary and non- dietary confounding factors, no significant relationship was found between dietary GI with HDL-C and LDL-C. There was also no statistically significant relationship between GI and total cholesterol or fasting Triacylglycerol. Conclusion: Findings of this study did not support the hypothesis of physiologic relevance of GI and lipid profile abnormality as a potential risk factor for atherosclerosis.